Статистичний аналіз диференціації доходів та рівня життя населення України: регіональний аспект - Аксьонова, Ірина Вікторівна (My University, 2019)
У статті узагальнено поняття «якість життя населення» та «рівень життя населення», розглянуто їх взаємозалежність. Зазначено, що якість життя є складовим компонентом рівня життя населення, який також включає умови життя й власне сам рівень життя. Наведено гранично критичні показники рівня життя, які використовуються у світовій практиці, представлено систему кількісних та якісних показників оцінювання рівня життя в національному вимірі. Проведено структурно-динамічний аналіз сукупних доходів та витрат домогосподарств України, який показав тенденцію до зниження рівня життя населення. Крім того, увага приділена аналізу диференціації доходів та витрат населення, а також зміні його якісного рівня життя за економічними районами та регіонами країни. Зроблено висновок про наявність розшарування населення регіонів країни за показниками доходів та рівня життя. Виявлено, що під час проведення досліджень рівня життя населення доцільно приділяти увагу тим показникам, на основі яких формується узагальнюючий показник якості життя країни.

The article summarizes the concepts of “quality of life of the population” and “standard of living of the population”, their interdependence. The category “quality of life” is a complex-structured concept, which is characterized by a multi-level system of indicators of the state and living conditions of the population in economic regions and regions of the country. At the same time, the quality of life is an integral component of the standard of living of the population, which also includes living conditions and the standard of living itself. The extreme-critical indicators of the standard of living, which are used in world practice, are presented, and a system of quantitative and qualitative indicators of the standard of living in the national dimension is presented. It is shown that the set of indicators on the basis of which it is advisable to assess and analyze the quality of life of the population of the country and its regions consists of both long-term values and the current needs of the population, its environment and social infrastructure. The article contains a dynamic analysis of the total income and expenditure of households in Ukraine, which showed a downward trend in the standard of living of the population. As a result of the structural analysis of total resources and expenditures of the population, it is revealed that the largest share in the structure of household resources is taken by cash income, among which the highest share belongs to wages. Among total expenditures, consumer aggregate expenditures take the largest share, among which food expenditures lead. In addition, attention is paid to the analysis of the differentiation of incomes and expenditures of the population on the basis of appropriate coefficients and changes in the quality of life of the population by economic regions and regions of the country. It is concluded that there is a separation of the population of the regions of the country in terms of income and living standards. It has been revealed that when conducting research on the standard of living of the population, it is advisable to pay attention to those indicators on the basis of which a generalized indicator of the quality of life of a country is formed.
Statistical analysis of differentiation of incomes and living standards of the population of Ukraine: regional aspect
Keywords: доходи населення; якість життя; рівень життя; показники диференціації доходів; індекс регіонального людського розвитку; статистичне оцінювання; incomes of the population; expenses of the population; quality of life; standard of living; indicators of income differentiation; regional human development index; statistical estimation